Mechanism of heat transfer in heterogeneous droplets of water under intense radiant heating; Journal of Engineering Thermophysics; Vol. 26, iss. 2 - Vysokomornaya O. V. Olga Valeryevna; Piskunov M. V. Maksim Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2017, 2017)
Title screen